2000
DOI: 10.1111/j.1471-0528.2000.tb11614.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of flexibility in routine antenatal care

Abstract: Objective To assess changes in satisfaction associated with a flexible approach to antenatal care schedDesign Randomised controlled trial.Setting Eleven primary care centres providing midwifery care in Avon.Participants Six hundred and nine women at low risk of obstetric complications presenting for antenatal care.Methods A standard antenatal care schedule ('traditional care') was compared with a schedule based on a minimum number of visits and additional visits with timing agreed between women and midwives ('… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 15 publications
0
35
2
Order By: Relevance
“…The characteristics of the sample are shown in the accompanying paper 1 . The data suggest that this was a predominantly privileged sample: the majority were living with their partners, were in employment and were nonsmokers.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The characteristics of the sample are shown in the accompanying paper 1 . The data suggest that this was a predominantly privileged sample: the majority were living with their partners, were in employment and were nonsmokers.…”
Section: Resultsmentioning
confidence: 97%
“…Details of centres, inclusion, recruitment and randomisation are given in the accompanying paper 1 . Women participating in the trial were asked to complete a questionnaire within one week of recruitment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronologically, they were quite close together (published 1996–2000). Women’s satisfaction levels were lower in three studies ([48–50]). Only one study showed a slight increase in satisfaction ([51]), although the sample size was very small ( n  = 43 intervention, n  = 38 control).…”
Section: Resultsmentioning
confidence: 99%
“…Maternal satisfaction is certainly one valid measure of outcome, but other consequences — maternal and paediatric, physical and psychological — must also be considered. Continuity of care is desirable from the maternal point of view, but it must be appropriate to the situation, and there must be understanding between all those participating, including women themselves, that sometimes transferring responsibility of care is in the best interests of the baby 24 . Within the hospital settings that most Australian women currently choose for the births of their babies, maternal satisfaction will be greatest, and outcomes for mothers and babies best, when midwives and obstetricians work in a complementary way, the first dealing largely with the normal, and the second largely with the abnormal.…”
mentioning
confidence: 99%